Analysis of Electric Field Distribution for High Voltage Transmission Line Glass Insulator in Clean Surface Condition using Finite Element Method - Abdullah Z.; Abidin I.Z.; Osman M.; Rahman N.A. (American Institute of Physics Inc., 2024)
This paper describes the electrical performance of an 11 kV high voltage transmission line glass insulator. The proposed two-dimensional model was designed using AutoCAD software in 2D. Glass insulator close to dry clean surfaces was considered. The behaviour of the electric field distribution along the creepage distance of a glass insulator under clean surface conditions was analysed using COMSOL Multiphysics software. The results show that the intensity of the electric field stress occurs near the end fitting parts and at a small radius of curvature. The electric field stress is not observed at the top of the glass insulator and at the end of the outer skirt. The strongest electric field strength is near the triple junction region (air-cap-glass) compared to the high-voltage-end terminal region. 2023 American Institute of Physics Inc.. All rights reserved.